Defective Human T-Cell Lymphotropic Virus Type I (HTLV-I) Provirus in 10 Chilean Seronegative Patients with Tropical Spastic Paraparesis or HTLV-I-Associated Myelopathy - Ramirez, Eugenio (American Society for Microbiology, 1998)
We studied the presence of tax and ltr genes from human T-cell lymphotropic virus type I (HTLV-I) provirus in the peripheral blood mononuclear cells from 15 seronegative patients with tropical spastic paraparesis or HTLV-I-associated myelopathy by PCR. Only a region of the tax gene from 10 patients was amplified. The nucleotide homologies of six Chilean isolates to the ATK-1 clone ranged between 98.7 and 99.4%.